COMMUNITY EMPOWERMENT THROUGH FOOD PROCESSING BASIC CHOCOLATE - Muliyati Muliyati; Haswan Yunaz; Irzan Soepriyadi (Dinasti Publisher, 2021)
Indonesia is a cocoa producer with potential to be developed. Cocoa that has been industrially processed into cocoa powder, dark chocolate and others. Chocolate-based cake business is very suitable to be developed because the raw materials are easy to obtain. In addition to the potential available raw materials, cocoa also contains good nutrition for the growth of the human body. The purpose of the training is to increase knowledge about entrepreneurship, improve welfare and improve nutrition for the community considering the current condition of the country which is being affected by the COVID-19 virus outbreak. The participants were attended by 20 people who were going to start a new cake business, especially cakes made from chocolate. The training material consists of theory and practice of making chocolate-based cakes. The results obtained from the technical guidance of this training are that the community has knowledge about the establishment of new businesses, especially the delicious, nutritious and hygienic chocolate cake business. All participants who take part in the training are willing to establish a new entrepreneur of chocolate-based cakes, either individually or in groups.